Alternatif abutment dan retensi pada prostetik implan (Laporan Kasus) - Julita; Rosalina Tjandrawinata (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Dental implant is one option that can be used to replace loss of one or more teeth with fixed restoration in restoring the function of mastication, esthetic, and phonetic in patients. An understanding of alternative abutment and retention in implant prosthetic is needed to complete the entire implant treatment. In the first case a 40-year-old female patient was rehabilitated with Nobel Replace Conical Connection TiUnite implant. Final prosthetic is hybrid screw-retained metal porcelain crown with esthetic abutment. The second case the 39-year-old female patient came to get implant treatment on 36 regio, had previously been implanted but failed. CBCT radiograph results the patient had installed three implants on the lower right and upper left side. The patient had no systemic disease. Type of implant is the same as the first case, but the prosthese used cement-retained metal porcelain crown with universal base abutment. The selection of abutment and retention in a good implant prosthetic is important and is a success factor in implant treatment.